2022
DOI: 10.3390/diagnostics12040848
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid RT-LAMP Assay for SARS-CoV-2 with Colorimetric Detection Assisted by a Mobile Application

Abstract: Loop-mediated amplification has been promoted for SARS-CoV-2 screening, however, antigen tests are preferred in low-income countries and remote zones. Poor training in molecular biology, plus the need for RNA purification or reading instruments to overcome issues of sensitivity in colorimetric detection, are some of the reasons limiting the use of this technique. In this study, nasopharyngeal swabs, aspirates and saliva were amplified in an in-house LAMP assay and subject to colorimetric detection, achieved by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…In addition, for each color capture (every 10 s) a standardized white light is emitted, guaranteeing that the same color pattern was captured. This is a clear advantage over smartphone capture, since the lightning exposure and equipment brand has a strong influence on the data acquisition [ 23 ]. Another advantage of our device is that it captures the data automatically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, for each color capture (every 10 s) a standardized white light is emitted, guaranteeing that the same color pattern was captured. This is a clear advantage over smartphone capture, since the lightning exposure and equipment brand has a strong influence on the data acquisition [ 23 ]. Another advantage of our device is that it captures the data automatically.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that if these steps weren’t followed, the RT-LAMP reaction color rapidly turned from pink to orange, indicating acidification of the solution due to the incorporation of atmospheric CO 2 . Another study that performed some of these procedures also saw an improvement in the stability of the color reaction [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The LAMP assay has several advantages over other nucleic acid amplification methods, such as being simple, sensitive, and rapid [ 12 ]. In addition, LAMP assays can be performed using a variety of detection methods, including colorimetric, lateral flow, fluorescence, and fluorescent probe detection [ 13 , 14 , 15 , 16 ]. Among these methods, fluorescent probe detection is particularly useful for the real-time monitoring of the LAMP reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The overall detection accuracy was enhanced when using the mobile application (75–86%) compared to the naked eye (61–74%). In contrast, the detection accuracy was 55, 70, and 80% for the nasopharyngeal swabs, aspirates, and saliva, respectively [ 22 ]. The abovementioned studies illustrated the possibility of using RT-LAMP with different sampling locations than the naso-oropharyngeal swabs.…”
Section: Introductionmentioning
confidence: 99%